TINJAUAN YURIDIS TERHADAP PERLINDUNGAN HUKUM MASYARAKAT ADAT ATAS HAK ULAYAT (STUDI KASUS: MASYARAKAT ADAT MEGOW PAK TULANG BAWANG DI LAMPUNG - Melvin Kurniawan Darma; Endang Pandamdari (Jurnal Hukum Adigama, 2021)
Land is the most essential asset of Indonesian, since all Indonesian live and grow up on the Land. Indonesian positioned the land as the most important especially for customary law societies. Customary communal land rights in customary law societies are very important for life continuation of customary law societies, however there are many customary communal land rights taken by irresponsible companies, even though customary communal land rights are recognized and protected according to Law of the Republic of Indonesia art. 18B verse (2) as a guideline that customary communal land rights are recognized and protected under Law of the Republic of Indonesia. This research also intends to find out the existence of customary communal land rights under the law. Provisions of art. 18B verse 2 declares recognition of customary communal land rights along with traditional rights. In this case government officers who take the customary communal land rights to create a company, plantation and others. Therefore many customary law societies do not accept when the customary rights are taken over by irresponsible individuals, resulting in a conflict between the two parties between the company and the customary law society. The government officers should have known that the Law recognized and protected the customary communal land rights. In this case, customary law societies, especially customary communal land rights, are recognized and protected by The Law of Republic of Indonesia 1945, Agrarian Principal Law, and many others laws.